Military Nursing in "Operation Return to Brazil": aeromedical evacuation in the coronavirus pandemic - Letícia Lima Borges; Clarissa Coelho Vieira Guimarães; Beatriz Gerbassi Costa Aguiar; Luiz Alberto de Freitas Felipe (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to describe the experience of military nursing in "Operation Return to Brazil" in an aeromedical evacuation. Method: this is an experience report of the nursing staff in the Aeromedical Evacuation of potentially-contaminated Brazilians who were in Wuhan, China, after the outbreak of the new coronavirus. Results: the report was constructed from nursing care performed in three stages: pre-flight, screening, and flight. Pre-flight care would include aircraft configuration and material prediction. In screening, the staff was concerned with being properly attired. In the health assessment of returnees, in-flight, attention was focused on Personal Protective Equipment handling to minimize the risk of contamination by prolonged contact with potentially-contaminated passengers. Final considerations: nursing was committed to planning all the actions of this mission, which was one of the longest, strenuous and unprecedented in the history of aeromedical transport in Brazil.